Domino-type progressive collapse analysis of a multi-span simply-supported bridge: A case study - Bi, Kaiming; Ren, W.; Cheng, P.; Hao, Hong (Pergamon, 2015)
Hongqi Viaduct, a multi-span simply-supported bridge in Zhuzhou city, Hunan Province, China, collapsed progressively during the mechanical demolishing of the bridge on May 17, 2009. Totally nine spans collapsed in the accident and it is a typical domino-type progressive collapse. The accident resulted in the loss of 9 lives and 16 injuries. Investigations were conducted after the accident to determine the cause of the unexpected progressive collapse. This paper is aimed at presenting a summary of the bridge before and after the incident, the demolishing plans and field investigations after the accident. To better understand the cause and mechanism of the progressive collapse, a numerical simulation is carried out. A detail 3D finite element (FE) model is developed by using the explicit FE code LS-DYNA. The bridge components including the bridge slabs, wall-type piers, longitudinal and transverse reinforcement bars are included in the model. The non-linear material behaviour including the strain rate effects of the concrete and steel rebar are considered. The model is used to simulate the bridge collapse induced by demolishing, and the domino-type progressive collapse of the bridge is clearly captured. Based on the numerical results, the reason for the failure is discussed and better understood. Finally, the possible mitigation methods of such progressive collapses of multi-span viaducts are suggested.